Re-branding strategy of IPDC Finance Limited and how it’s helping the company to become sustainable - Yasmin, Mahfuja (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.